Sikap Irlandia Pasca Kemerdekaan Israel, Studi Kasus: Konflik Israel-Palestina - Nurul Achyar Fauzi; Reni Windiani; Shary Charlotte Pattipelohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Since the establishment of Republic of Ireland, their foreign policy is neutral. For examplein world war II, when most of the European country at war (either as allied force, or axispower), Ireland prefer not favoring any side. However, in the Israel-Palestine conflict IrishGovernment doesn’t look as a neutral country, Ireland seems against with Israel. Ireland isa supporters of Israel previously, but soon after Israel independence Ireland changed theirsupport to Palestine. This research aim to analyze Irish respond after Israel independence,with case study: Israel-Palestine conflict. To analyze Ireland foreign policy in Israel-Palestine conflict, this research using neo-realist theory and interest group theory. Themethod that is used in this research is qualitative method with descriptive-analytical typethrough interviews and literature technics. Outcomes from this research is: there is anational interest that Ireland want to accomplished from this conflict. Other than that thereis two factors that influencing Ireland policy in this conflict, that is internal and externalfactor. In internal factor, Nationalist group is influencing Ireland foreign policy. In externalfactor, there is “Vatican factor” that influencing Ireland policy in this conflict.